The Replication Stress Response on a Narrow Path Between Genomic Instability and Inflammation - Técher, Hervé; Pasero, Philippe (Frontiers in Cell and Developmental Biology, 2021)
The genome of eukaryotic cells is particularly at risk during the S phase of the cell cycle, when megabases of chromosomal DNA are unwound to generate two identical copies of the genome. This daunting task is executed by thousands of micro-machines called replisomes, acting at fragile structures called replication forks. The correct execution of this replication program depends on the coordinated action of hundreds of different enzymes, from the licensing of replication origins to the termination of DNA replication. This review focuses on the mechanisms that ensure the completion of DNA replication under challenging conditions of endogenous or exogenous origin. It also covers new findings connecting the processing of stalled forks to the release of small DNA fragments into the cytoplasm, activating the cGAS-STING pathway. DNA damage and fork repair comes therefore at a price, which is the activation of an inflammatory response that has both positive and negative impacts on the fate of stressed cells. These new findings have broad implications for the etiology of interferonopathies and for cancer treatment.